KUALITAS PELAYANAN LABORATORIS KRIMINALISTIK BARANG BUKTI KEPADA PENYIDIK - Aldiansyah, Mochammad; Rianto, Joko; Hardian, Dafyar Eliadi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This study aims to analyze the quality of forensic laboratory services related to physical evidence provided to regional investigators at the Forensic Laboratory Center of the Criminal Investigation Agency of the Indonesian National Police or known as Puslabfor Bareskrim Polri in Bogor. Data were collected through in-depth interviews, direct observation, and documentation involving laboratory personnel and investigators. The findings reveal that four of the five service quality dimensions are well-implemented. Reliability is reflected in the staff's ability and accuracy in conducting evidence examinations. Assurance shows that personnel possess high competence and instill confidence in investigators. Tangibles indicate that facilities and laboratory equipment are adequate and well-maintained. The empathy dimension reveals the staff’s concern for the needs and challenges faced by investigators. However, the responsiveness dimension still needs improvement, particularly in terms of timely and accurate responses to service requests, which are hindered by administrative processes and workload constraints. The study concludes that the overall service quality at Puslabfor is satisfactory. Improving the responsiveness dimension is essential to enhancing service efficiency and investigator satisfaction. These findings are expected to contribute to the advancement of science-based public services within the police institution. Keywords: Service Quality, Puslabfor, Physical Evidence, Investigator, RATER